1992
DOI: 10.1152/ajpendo.1992.263.6.e1054
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of V1a vasopressin receptors by glucocorticoids

Abstract: WRK1 cells (a rat mammary tumor cell line) exhibit a vasopressinergic receptor of V1a subtype tightly coupled to phospholipase C. Addition of dexamethasone to the culture medium principally potentiated the vasopressin-sensitive accumulation of inositol phosphates and to a lesser extent the NaF-sensitive phospholipase C activity. On the opposite, such treatment was without effect on the basal level of intracellular inositol phosphates or on bradykinin- or serotonin-sensitive phosphoinositide metabolisms. Glucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…In vitro studies have shown that incubation of vascular smooth muscle cells with dexamethasone enhances the increase in IP formation by these hormones (42,43), though others using a similar experimental system have reported uncoupling of the Ang II receptor by glucocorticoids (44). In contrast to the pituitary V1b-R, vascular smooth muscle Ang and V1a receptors increase after in vitro incubation with glucocorticoids (45,46), which would also contribute to the sensitizing action of glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that incubation of vascular smooth muscle cells with dexamethasone enhances the increase in IP formation by these hormones (42,43), though others using a similar experimental system have reported uncoupling of the Ang II receptor by glucocorticoids (44). In contrast to the pituitary V1b-R, vascular smooth muscle Ang and V1a receptors increase after in vitro incubation with glucocorticoids (45,46), which would also contribute to the sensitizing action of glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…In other vertebrates, neural AVT protein and pro-AVT mRNA levels are both regulated by gonadal steroids [21,43], and gonadal steroids and glucocorticoids have been shown to regulate AVT/AVP receptor density in select brain regions of mammals (e.g., [7,29,68,71]). AVT receptor mRNAs in the hindbrain have been shown to vary seasonally in teleosts [62], but no study has yet examined whether v1a2 gene transcription in the teleost brain is regulated by steroid hormones.…”
Section: Variation In V1a-type Receptor Mrna Abundance Among Sexual Pmentioning
confidence: 99%
“…The elevation of mRNA levels precedes the rise in binding activity, suggesting a transcriptional effect. Furthermore, it has been reported that GC amplify the vasopressin-induced transduction signal (increased IP accumulation in the presence of dexamethasone) (312,313). At the protein level, GC have been shown to produce an early decrease in binding site density, followed later by an increase, which becomes more prevalent with time.…”
Section: A Tissue-specific Expression and Regulation Of Membrane Hormentioning
confidence: 99%